Synthesis of nanocomposite coating based on TiO2/ZnAl layer double hydroxides - Jovanov, V.; Rudic, O.; Ranogajec, J.; Fidanchevska, E. (Editorial CSIC, 2017)
The aim of this investigation was the synthesis of nanocomposite coatings based on Zn-Al layered double hydroxides (Zn-Al LDH) and TiO2. The Zn-Al LDH material, which acted as the catalyst support of the active TiO2 component (in the content of 3 and 10 wt. %), was synthesized by a low super saturation co-precipitation method. The interaction between the Zn-Al LDH and the active TiO2 component was accomplished by using vacuum evaporation prior to the mechanical activation and only by mechanical activation. The final suspension based on Zn-Al LDH and 10wt. % TiO2, impregnated only by mechanical activation, showed the optimal characteristics from the aspect of particle size distribution and XRD analysis. These properties had a positive effect on the functional properties of the coatings (photocatalytic activity and self-cleaning efficiency) after the water rinsing procedure.